Detecção de genes de entrotoxinas de Staphylococcus aureus e estafilococos coagulase negativos isolados de leite bovino e de tanques de refrigeração comunitários procedentes de pequenas propriedades da região de Bauru-SP - Lemos, Fabio Almeida de [UNESP] (2015)
This study aimed at the isolation of Staphylococcus aureus and coagulase-negative staphylococci, from bovine milk samples, associated with cases of subclinical mastitis detected in ten small properties from Bauru - SP. Also, determine the antimicrobial susceptibility of the agents isolated and to investigate the presence of enterotoxin gene and the mecA gene of oxacillin resistance from the bacterial strains, and milk samples from bulk tanks . Of 105 samples obtained, 55 ( 52.4 %) were coagulase positive staphylococcus (CPS) and 50 (47.6%) coagulase negative staphylococcus (CNS). Among the CPS, S. aureus was isolated in most cases, 48 ( 87.3 %). Of the 12 CNS species isolated, the most frequent were S. warneri, S. hyicus, both with 8 (16%) and S. xylosus 7 (14%) . The highest levels of antibiotics resistance were observed for the group of β - lactam antibiotics - penicillin 92.7% and ampicillin 90.9% CPS and ECN - 56 % and 52 % respectively. The greatest sensitivity of the CPS strains was to cephalexin, and for CNS isolates to enrofloxacin. From the cases of subclinical mastitis, genes encoding enterotoxins were found in, 17/142 (12%) . The sea gene was the most prevalent being detected in 11 ( 7.7 %). The seb gene was detected in five (3.5%) samples, and in one sec (0.7%). All were negative for sed gene. When we consider the results directly from cultures of Staphylococcus spp. isolated from subclinical mastitis, there was only the gene sec in 8/105 (7.6%).From these isolates of Staphylococcus spp., positive for sec 05/105 (4.8%) were CPS, (03 S. aureus and 02 S.intermedius) and 03/105 (2.8%) CNS, (01 S. xylosus, 01 S.hyicus and 01 S.lugdunensis). To sea, seb and sed samples were negative. Of the ten samples from the bulk tanks, 02/10 (20%) were positive for sea and 01/10 (10%) to seb. The mecA gene was detected in three strains of S. aureus, representing 6.2% of the total of 48 S. aureus strains isolated. The identification ...